Jurimetrics in the Reconstruction of the Joint Property Division Model for Wage-Earner Wives in Indonesia - Rouf, Abd. (Al-Ahkam, 2024)
The joint property division in Article 97 of the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) is one-half (1/2) as long as it is not specified otherwise in the marriage agreement. This is followed mainly by judges because of the legal certainty in it, but not for wives with double burdens who work to earn a living and are also housewives. This research aims to reconstruct the joint property division through jurimetrics analysis to obtain more objective and tested results because it is based on empirical data. This research is a normative law study with a descriptive approach. The data in this study are the Compilation of Islamic Law, and concepts, as well as other laws and regulations related to the joint property division analyzed with jurimetrics to get the ideal formulation and scale of division. The results obtained include several models of joint property division for wage-earner wives (breadwinners) along with the scale of formulation which are divided into two groups, namely the joint property division with a share of one-half for the former husband and wife and the joint property division with a share other than one-half for the former husband and wife according to the role taken by both. This research can be used as a reference by judges in deciding cases of joint property, especially related to the condition that a wife is a wage-earner.